Capnocytophaga ochracea detected in cerebrospinal fluid of a meningioma patient: a case report - Le Zhang; Jingyi Hu; Ying Xin; Han Cheng; Yan Yan; Qin Wang (BMC Infectious Diseases)
Abstract Capnocytophaga ochracea (C. ochracea) is a species of Gram-negative and facultative anaerobic bacterium. It was first reported in 1979 and isolated from both healthy and diseased sites in the oral flora. The bacteria can cause septicemia, endocarditis, endometritis, blepharoconjunctivitis and other infections. Herein, we present the first cerebrospinal fluid (CSF) infection case caused by C. ochracea in humans. Gram-negative fusiform, non-spore forming rods were detected in an anaerobic bottle of CSF culture obtained from a 50-year-old man who had been hospitalized for meningioma in Tianjin Huanhu Hospital. Although the organism could not be identified using a conventional method, it was finally identified as C. ochracea based on the results of metagenomics next generation sequencing, matrix-assisted laser desorption ionization time-of-flight mass spectrometry and 16 S rDNA sequencing analysis. Subsequently, Streptococcus oralis was also detected in the CSF of the patient. The patient was treated with meropenem and vancomycin, and the infection was well controlled. The clinically rare C. ochracea can be pathogenic in central nervous system of humans.